Productive and reproductive performance of Black Bengal Goat under farming condition in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was undertaken to evaluate the productive and reproductive performances of Black Bengal Goat (BBG) under farming condition. Data were collected from Bangladesh Livestock Research Institute (BLRI) goat research farm during 2006 to June 2013. Data were analyzed by SPSS version 17.0 statistical computerprogram. The mean of birth weight of kid irrespective ofsex was 1.31 kg. Live weights at 3, 6, 9 and 12 months were 5.65, 9.63, 14.20 and 17.70 kg, respectively. Weaning weight was heavier in second generation (G2) (5.34 kg) followed by 5.15 kg in first generation (G1), 4.87 kg in third generation (G3) and 4.17 kg in foundation stock (G0) with an overall mean of 4.88 kg. Body weight gain at 0-3 month, 3-6 month, 6-9 month, and 9-12 month ages were 66.34±1.69 g/d, 41.54±2.02 g/d, 49.97±3.10 g/d and 39.28±4.35 g/d, respectively. Body weight gain from 0-12 month age was 56.31±1.40 g/d. Average daily milk yield, lactation length and total milk per lactation were 287.7 ml/d, 61.5 days and 19129.40 ml, respectively. Average age and weight at puberty were 182.7±7.25 days and 9.81±0.34 kg, respectively. Age and weight at 1st service were 187.56±8.33 days and 9.91±0.39 kg, respectively. Number of services per conception was 1.37±0.03. Average litter size, gestation length, post partum heat period, days open and kidding interval were 1.75±0.03, 142.45±0.31 days, 33.39±1.82 days, 46.62±2.86 days and 188.01±2.14 days, respectively. The results indicate that despite of having promising prolificacy and breeding and reproductive efficiency of BBG, still there need to be improved for birth weight, weight gain and milk yield of dam.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 235-245